Karbala in Turkish literature, a study in the spatial dimension: ادب مقارن - جليل صاحب خليل م. د. (lark, 2020)
This research seeks to reveal the spatial image of Karbala in the Turkish poetry scene through an approach that follows a comparative methodology. It is trying to determine the points of convergence between the image of Karbala as a summoned historical discourse and the Turkish poetic discourse that emerged from a special understanding of Karbala with its spatial dimension and the ideological shades it carried, especially those that transformed it from the real area to the imagined and ideological one. In light of its advanced strategy, the research proceeded according to a plan in which it was divided into two topics. As for the first, it was busy providing a theoretical survey of the terminological title materials (Karbala - The Spatial Dimension - The History of Turkish Literature), while the other formed a field that accommodated the applied procedural moves, and revealed the most important manifestations of the dimension and its symbolism, which recorded an effective presence in the readable text. It also indicates that the poets were influenced by the Arabic and Islamic names of ideological figures, sacred places, and historical narratives in relation to the Ahl al Bayt (peace be upon them).